Christian Family, Christian Nation: Raymond Johnston and the Nationwide Festival of Light in Defence of the Family. (4th January 2016) - Atherstone, Andrew
Abstract : 'We reject that morality – death to the family!' So interjected a young female heckler during the inaugural rally of the Nationwide Festival of Light (NFOL) in Westminster Central Hall on 9 September 1971. Although press coverage of the event focused upon more dramatic interventions, such as the attempt by a group of bogus nuns to storm the platform, it was this stark proclamation of 'death to the family' which revealed the primary ideological battleground in the NFOL's morality campaigns of the 1970s. Six months later, Bishop Maurice Wood of Norwich told the follow-up 'Land Aflame' rally in March 1972 that 'in this day of synthetic substitutes there is no substitute for the family'. NFOL was sometimes accused of fighting simultaneously on too many fronts, ranging from pornography and blasphemy to religious education and Sunday trading, but Eddy Stride (rector of Christ Church, Spitalfields, and chairman of the NFOL executive committee) summarized the movement's purpose as being 'to actively promote the values of human dignity expressed in the Biblical view of family life'.